2008
DOI: 10.1177/1076029608316013
|View full text |Cite
|
Sign up to set email alerts
|

Association of Angiotensin-Converting Enzyme Gene 2350G>A Polymorphism With Myocardial Infarction in a Chinese Population

Abstract: Angiotensin-converting enzyme (ACE) gene 2350G>A polymorphism has the most significant effect on plasma ACE concentrations. But the association between this polymorphism and myocardial infarction (MI) is presently unknown. We carried out a case-control study in the Chinese Han population. ACE2350G>A genotypes of 231 patients with MI and 288 healthy controls were detected by PCR-RFLP. Differences in frequencies of ACE genotypes and alleles and their associations with clinical features were assessed. The distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Measurements of high-sensitivity CRP (hs-CRP), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TGs) were performed as described previously. 31 Interleukin 6 was measured by a high-sensitivity enzyme-linked immunosorbent assay assay from R&D Systems (Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of high-sensitivity CRP (hs-CRP), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TGs) were performed as described previously. 31 Interleukin 6 was measured by a high-sensitivity enzyme-linked immunosorbent assay assay from R&D Systems (Minneapolis, MN).…”
Section: Methodsmentioning
confidence: 99%
“…Previous case-control studies have shown that the frequency of the A allele in Chinese healthy controls is 0.417-0.451 (19,23,24). The A allele frequency in Chinese subjects was significantly greater ( p <0.05) than those in a Pakistani population (0.298) (34) and a Malaysian cohort (0.207) (35) but lower ( p <0.05) than those in a European sample (0.513–0.542) (36) and an Iranian sample (0.591) (37).…”
Section: Discussionmentioning
confidence: 99%
“…The samples were then centrifuged at 2500 rpm for 30 minutes at 4°C and immediately stored at -80°C until analysis. The measurement of total cholesterol (TC), high-density lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), and triglycerides (TG) was performed as described previously (7,19). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations